ANTIHYPERGLYCEMIC ACTIVITY OF CHARANTIN-RICH EXTRACT FROMTHE FRUITS OF Momordica charantia Linn. IN in vitro AND in vivo STUDIES (Applied Biological Research, 2024)
Momordica charantia Linn. (Bitter gourd or Karela) fruits are one of the common vegetable consumed in India; traditionally used for the management of blood glucose levels (BGL) in diabetes. The present study aimed to evaluate the antihyperglycemic potential of charantin-rich extract from the fruits of bitter gourd in in-vitro enzyme inhibition assay (α-amylase and α-glucosidase) and in-vivo using carbohydrate-challenged normal and STZ-induced diabetic rats. The bitter gourd fruits were extracted using an ultrasonicator and the extract was assayed for the charantin content using the HPTLC method. The standardized extract of M. charantia (SMC) contained 0.34±0.15% w/w charantin. The charantin-rich extracts of M. charantia showed concentration-dependent inhibition of α-amylase and α-glucosidase enzymes with IC50 values 1.41±0.17 and 2.29 ± 1.84 mg/mL, respectively. In starch and sucrose challenged normal rats, pre-treatment with SMC (200 mg/kg, b.w.) produced 13.04% and 16.32% reduction in peak BGL compared to the negative control. In starch and sucrose-challenged diabetic rats (induced by a single intraperitoneal injection of streptozotocin, 50 mg/kg, b.w.), pre-treatment with SM at a dose of 200 mg/kg, b.w. produced 7.44% and 8.32% reduction in peak BGL when compared with toxic control. The study results provided scientific evidence for the fact that bitter gourd fruits are effective in the management of BGL in diabetes which can be mainly attributed to charantin.
Keywords: Momordica charantia; bitter gourd; charantin; HPTLC; Diabetes